Evaluation of the influence of microwaves radiation on a biomaterial composed of three phases of calcium phosphates - Rodriguez Chanfrau, Jorge E. [UNESP] (Biointerface Research Applied Chemistry, 2020)
The chemical similarity with the bone components that calcium phosphates present have been the fundamental cause of their use as biomaterials in the regeneration processes, presenting good biocompatibility, bioactivity and osteoconductivity. Among the biomaterials studied from calcium phosphates, there are multiphase biomaterials, which are those that contain two or more phases of calcium phosphates in their composition. These mixtures improve the chemical-physical and biological properties of these materials. The use of biomaterials in the regeneration process requires previously eliminating the microorganisms present in the material, through a sterilization process. Different sterilization methodologies have been applied to decontaminate biomaterials, including the use of microwave radiation. The objective of this study was to evaluate the influence of the MW radiation application of a multi-phase biomaterial made of a three-phase mixture of calcium phosphates synthesized by wet chemical method. The results of this study showed that the application of MW radiation to ceramic samples containing the OCP phase causes the thermal decomposition of this phase, modifying its crystallinity index. This aspect should be taken into account when applying sterilization by applying MW radiation to ceramic samples with characteristics similar to those studied in this work.
Keywords: Biomaterials; Calcium phosphates; microwave radiation; mixture of calcium phosphates; synthesis